Desiccation tolerance of seeds of species of Eugenia - Delgado, Liliana Ferreira; Barbedo, Claudio José (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the desiccation tolerance of seeds of six fruit species of Eugenia (E. brasiliensis Lam., E. cerasiflora Miq., E. involucrata DC., E. pyriformis Camb., E. umbelliflora Berg. and E. uniflora L.) aiming to provide information for the conservation of the germinability of these seeds during storage. Seeds were dried continuously in oven (40ºC) or closed chambers with silica gel (25ºC) until 10% water content. After drying, samples of the seeds were analyzed for water content and germination. As water content decreased, seeds lost viability, independently of the drying method. Seeds from each species differed on sensitivity to desiccation, but all seeds were intolerant to levels lower than 45% water content and lost viability at levels lower than 15%.